1998
DOI: 10.1021/bi9817414
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Microtubule Dynamics by Binding of Cemadotin to Tubulin:  Possible Mechanism for Its Antitumor Action

Abstract: Cemadotin (LU103793) (NSC D-669356) is a water-soluble synthetic analogue of dolastatin 15 that inhibits cell proliferation in vitro and the growth of human tumor xenografts. Cemadotin is in phase II clinical trials as a promising cancer chemotherapeutic agent. The drug blocks cells at mitosis. Its primary mode of action has been unclear but is believed to involve an action on microtubules. We have found that cemadotin binds to tubulin and strongly suppresses microtubule dynamics. Scatchard analysis of cemadot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 33 publications
0
26
0
1
Order By: Relevance
“…In contrast, it is difficult to demonstrate the binding of [ 3 H]dolastatin 15 to tubulin; such binding is only demonstrable by HummelDreyer chromatography. Analogously, Jordan et al (1998) examined the binding to tubulin of an analog of dolastatin 15, All reaction mixtures contained 10 M (1.0 mg/ml) tubulin, 0.4 mM GTP, varying concentrations of peptides, and 4% (v/v) dimethyl sulfoxide. Polymerization was followed for 20 min at 30°C.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it is difficult to demonstrate the binding of [ 3 H]dolastatin 15 to tubulin; such binding is only demonstrable by HummelDreyer chromatography. Analogously, Jordan et al (1998) examined the binding to tubulin of an analog of dolastatin 15, All reaction mixtures contained 10 M (1.0 mg/ml) tubulin, 0.4 mM GTP, varying concentrations of peptides, and 4% (v/v) dimethyl sulfoxide. Polymerization was followed for 20 min at 30°C.…”
Section: Discussionmentioning
confidence: 99%
“…The results from the competitive binding experiments revealed that PBOX-6 did not inhibit binding of either colchicine or vinblastine to tubulin, indicating that PBOX-6 has its molpharm.aspetjournals.org own, novel, binding site upon tubulin. Other antimicrotubule agents, such as estramustine (Panda et al, 1997), arsenic trioxide (Ling et al, 2002), naphthopyran (Dell, 1998), and cemadotin (Jordan et al, 1998), have also been shown to bind to as-yet-uncharacterized novel sites on tubulin.…”
mentioning
confidence: 99%
“…This metabolite also prevents microtubule assembly in microtubule polymerization assays, but exhibits 8-fold less cytotoxicity than cemadotin in vitro (9). Tasidotin was rapidly cleared from plasma with an effective half-life of <45 minutes in most cases, whereas ILX651-C-carboxylate concentrations peaked at 5 hours and had a half-life of f10 hours.…”
Section: Discussionmentioning
confidence: 96%
“…Cemadotin, a dolastatin-15 pentapeptide, at concentrations as low as 10 to 100 nmol/L, suppressed the rate of tubulin growth more than shortening, a process that differentiated dolastatin-15 analogues from other tubulin-acting agents like Vinca alkaloids (which suppress the rate of growth and shortening simultaneously) and taxanes (which preferentially suppress the rate of tubulin growth; ref. 9). However, clinical trial results with cemadotin were disappointing due to rapid metabolic conversion and dose-limiting cardiovascular toxicity, including hypertension, angina, and myocardial infarction (10 -13).…”
Section: Tasidotin (Nn-dimethyl-l-valyl-l-valyl-n-methyl-l-valyl-l-mentioning
confidence: 99%